Method for manufacturing bath shaft member
Patent Information
- Application Number
- JP2023127676
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0015】 本発明によれば、浴中軸部材の表面の耐摩耗性を向上させることができるため、使用とともにビード状の部分的な損耗が発生することを防止できる。
Smart Images

Figure 2025023508000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a shaft member for use in a hot-dip metal plating bath. [Background technology]
[0002] When manufacturing a hot-dip metal-coated steel sheet, such as a hot-dip galvanized steel sheet, a coating is formed on the surface of the steel sheet in the process of immersing the steel sheet in a hot-dip metal coating bath and pulling the steel sheet upward by changing the direction of travel of the steel sheet with a sink roll placed in the bath (see, for example, Patent Document 1 below). The sink roll is rotatably held in the hot-dip metal coating bath and rotates when the steel sheet is transported.
[0003] Both ends of the sink roll are rotatably supported by bearings. Specifically, cylindrical sleeves are placed on both ends of the shaft of the sink roll, and the sleeves are supported by bearings. As a result, when the sink roll rotates, the surface of the sleeve slides against the bearings. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Utility Model Application Publication No. 5-69155 Summary of the Invention [Problem to be solved by the invention]
[0005] A sleeve, which is an example of a bath-immersed shaft member, is susceptible to wear and deterioration because its surface is in sliding contact with a bearing. Therefore, it is considered to form a build-up layer on the surface of the sleeve to improve wear resistance. For example, it is considered to form a build-up layer on the surface of the sleeve using PTA (Powder Plasma Transferred Arc Welding), but it has been confirmed that the build-up layer formed by PTA generates bead-shaped partial wear with use.
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a method for manufacturing an immersion shaft member capable of improving the wear resistance of the surface of the immersion shaft member. [Means for solving the problem]
[0007] (1) The manufacturing method of a bath-centered shaft member according to the present invention is a manufacturing method of a bath-centered shaft member used in a molten metal plating bath, and includes a cladding process of forming a cladding layer on a surface of the bath-centered shaft member by laser cladding using a composite alloy containing a cobalt-based alloy and tungsten carbide as a molten material.
[0008] According to this configuration, by forming a build-up layer on the surface of the bath shaft member using laser cladding, it is possible to reduce the uneven dispersion caused by the specific gravity difference between the cobalt-based alloy and tungsten carbide, and form a build-up layer in which the tungsten carbide is uniformly dispersed. This improves the wear resistance of the surface of the bath shaft member, thereby preventing the occurrence of bead-shaped partial wear with use.
[0009] (2) The cobalt-based alloy may contain a carbide-forming element or an intermetallic compound-forming element.
[0010] According to this configuration, a buildup layer having improved wear resistance can be formed by using a cobalt-based alloy containing a carbide-forming element or an intermetallic compound-forming element.
[0011] (3) When the cobalt-based alloy contains a carbide-forming element, the content of the tungsten carbide in the welding material may be 30 vol% or more. In this case, the build-up step may be performed with a laser output of 900 to 1000 W. When the build-up step further includes a lowering step of forming an underlay layer on the surface of the bath-in-shaft member, the build-up step may be performed with a laser output of 600 to 1400 W on the surface of the underlay layer.
[0012] According to this configuration, a cobalt-based alloy containing carbide-forming elements can be used to form a buildup layer free of defects such as blowholes and insufficient fusion, thereby effectively improving the wear resistance of the surface of the bath shaft component.
[0013] (4) When the cobalt-based alloy contains an element that forms an intermetallic compound, the content of the tungsten carbide in the welding material may be 30 vol% or more. In this case, the build-up process may perform laser cladding at a laser output of 800 to 1400 W. When the build-up process further includes an underlay process of forming an underlay layer on the surface of the bath shaft member, the build-up process may perform laser cladding on the surface of the underlay layer at a laser output of 600 to 1400 W.
[0014] According to this configuration, a build-up layer free of defects such as blowholes and incomplete fusion can be formed using a cobalt-based alloy containing elements that form intermetallic compounds, thereby effectively improving the wear resistance of the surface of the bath shaft member. Effect of the Invention
[0015] According to the present invention, the wear resistance of the surface of the shaft member in the bath can be improved, so that the occurrence of bead-like partial wear that occurs with use can be prevented. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram showing an example of the configuration of a manufacturing apparatus for a hot-dip metal-plated steel sheet. [Diagram 2] FIG. 2 is a side view showing an example of the configuration of a sink roll, with a portion shown in cross section. [Diagram 3] FIG. 1 is a diagram for explaining laser cladding. [Figure 4] 13 is an image showing a cross-sectional observation result of a buildup layer. [Diagram 5] 13 is an image showing a cross-sectional observation result of a buildup layer. [Figure 6]13 is an image showing a cross-sectional observation result of a build-up layer when an underlay layer is formed. [Figure 7] These images compare PTA and laser cladding, where (a) shows a cross-section of a build-up layer formed by PTA, and (b) shows a cross-section of a build-up layer formed by laser cladding. [Figure 8] FIG. 2 is a schematic diagram showing a cross section of a buildup layer formed by PTA. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1. Hot-dip metal coated steel sheet manufacturing equipment Fig. 1 is a schematic diagram showing an example of the configuration of a manufacturing apparatus for hot-dip metal-coated steel sheets. This apparatus is for manufacturing hot-dip galvanized steel sheets, which are an example of hot-dip metal-coated steel sheets, and includes a molten metal bath 1, a snout 2, a sink roll 3, and a support roll 4.
[0018] In the molten metal bath 1, hot-dip galvanizing is stored as a molten metal coating, and a sink roll 3 and a support roll 4 are disposed in this molten metal coating bath. The snout 2 is for continuously feeding the steel sheet S into the molten metal bath 1, and the steel sheet S continuously passes through the snout 2, the interior of which is filled with an inert gas such as nitrogen.
[0019] The sink roll 3 is held rotatably about a rotation axis 5 extending horizontally. The steel sheet S is transported along the surface of the sink roll 3, thereby changing its traveling direction and being pulled upward. The sink roll 3 may be rotated by a drive source, or may be rotated by frictional force received from the steel sheet S being transported.
[0020] A pair (two) of support rolls 4 are provided, and each support roll 4 is held rotatably about a horizontally extending rotation axis 6 so that the surfaces of the pair of support rolls 4 abut against each other. The steel sheet S that has passed through the sink roll 3 is pulled upward through between the pair of support rolls 4 and transported out of the hot-dip metal coating bath. The pair of support rolls 4 may be rotationally driven by a drive source, or may be rotated by frictional force received from the steel sheet S being transported.
[0021] 2. Sync Roll Configuration 2 is a side view, partially in cross section, showing an example of the configuration of the sink roll 3. The sink roll 3 (including the rotating shaft 5) is made of a metal such as stainless steel. Both ends of the rotating shaft 5 of the sink roll 3 are covered with sleeves 7, and the sleeves 7 are held by bearings 8.
[0022] The sleeve 7 is a cylindrical member made of a metal such as stainless steel. The inner diameter of the sleeve 7 is approximately equal to the outer diameter of the rotating shaft 5 of the sink roll 3. The rotating shaft 5 is fitted into the sleeve 7, whereby the sleeve 7 is fixed to the rotating shaft 5. Therefore, when the sink roll 3 rotates, the sleeve 7 also rotates in conjunction with the rotation of the rotating shaft 5.
[0023] The bearing 8 is a cylindrical member made of a metal such as ceramic or stainless steel. The material of the bearing 8 may be the same as that of the sleeve 7, or may be a different material. The bearing 8 may be a single cylindrical member, or may be a cylindrical structure formed by combining a plurality of members. The inner diameter of the bearing 8 is slightly larger than the outer diameter of the sleeve 7. Therefore, when the sink roll 3 rotates, the outer peripheral surface of the sleeve 7 slides against the inner peripheral surface of the bearing 8 as the rotating shaft 5 rotates. The bearing 8 is supported by a support member 9. A flange portion 81 that protrudes in the radial direction is formed at one end of the bearing 8, and the flange portion 81 prevents the bearing 8, which is inserted into an opening formed in the support member 9, from falling out of the opening.
[0024] The sleeve 7 is an example of an in-bath shaft member used in a molten metal plating bath. However, other shaft members used in a molten metal plating bath, such as the bearing 8, are also included in the concept of an in-bath shaft member.
[0025] 3. Sleeve manufacturing method A method for manufacturing the sleeve 7, which is an example of a bath-immersed shaft member, will be specifically described below. The method for manufacturing the sleeve 7 according to this embodiment includes a cladding process for forming a cladding layer on the surface (outer peripheral surface) of the sleeve 7 by laser cladding using a composite alloy containing a cobalt-based alloy and tungsten carbide (W2C or WC) as a melting material.
[0026] Examples of cobalt-based alloys (matrix materials) contained in the composite alloys used as welding materials are shown in Table 1 below.
[0027] [Table 1]
[0028] Materials A to E are examples of cobalt-based alloys containing carbide-forming elements. Specifically, materials A to E all contain carbon (C) and chromium (Cr) in addition to cobalt (Co). Materials A to E also contain at least one of molybdenum (Mo), tungsten (W), silicon (Si), and boron (B).
[0029] Materials F and G are examples of cobalt-based alloys containing elements that form intermetallic compounds. Specifically, both materials F and G contain chromium (Cr) in addition to cobalt (Co), but do not contain carbon (C). Material F contains molybdenum (Mo) and silicon (Si), and material G contains iron (Fe).
[0030] 3 is a diagram for explaining laser cladding. In laser cladding, a laser processing head 100 is placed opposite the surface (outer circumferential surface) of the sleeve 7, and a build-up layer is formed in a spiral shape on the surface of the sleeve 7 while rotating the sleeve 7 around its axis.
[0031] A laser beam 101 is used as a heat source in laser cladding. The laser beam 101 is continuously emitted from a laser processing head 100 and irradiated onto the surface of the sleeve 7. The laser beam 101 may be a parallel beam or may be focused toward an irradiation position 104.
[0032] From the laser processing head 100, a laser beam 101 is emitted while continuously spraying a welding material 102 and a shielding gas 103 toward the surface of the sleeve 7. The welding material 102 is sprayed using a carrier gas. As the carrier gas and the shielding gas 103, for example, an inert gas such as argon gas or helium gas is used. The welding material 102 sprayed from the laser processing head 100 is incident into the shielding gas 103, so that oxidation during flight can be suppressed. However, the shielding gas 103 may be omitted.
[0033] 4. Laser cladding test In the following, we will explain the results of a test in which a cladding layer was formed on the surface of a base material by laser cladding using a composite alloy containing a cobalt-based alloy and tungsten carbide as the welding material, and the cladding layer was observed. The basic conditions are as shown in Table 2 below.
[0034] [Table 2]
[0035] Stainless steel (SUS316L) was used as the base material, which was preheated to a temperature of over 600°C, and then a build-up layer was formed on the surface of the base material. When forming the build-up layer, the movement of the laser processing head moving parallel to the base material was considered as one pass, and the position of the laser processing head was shifted relative to the base material by a specified feed amount for each pass, forming three passes (three rows) of build-up layers. Each row consisted of a single build-up layer, but adjacent build-up layers were formed so that they partially overlapped each other, preventing gaps from occurring between the build-up layers in each row.
[0036] The working distance of the laser beam emitted from the laser processing head was 25 mm. The shielding gas was sprayed from the laser processing head at a flow rate of 50 L / min, and the carrier gas was sprayed at a flow rate of 7 L / min. The feed amount for each pass was 3 mm, and the welding length for each pass was 50 mm. The specific test conditions are as shown in Table 3 below.
[0037] [Table 3]
[0038] The welding materials used were composite alloys with a matrix material being material A containing a carbide-forming element or material G containing an intermetallic compound-forming element. The welding materials containing material A contained 50 vol%, 40 vol%, and 30 vol% tungsten carbide. The welding materials containing material G contained 50 vol%, 40 vol%, and 30 vol% tungsten carbide. The specific gravity of material A was 8.30 g / cm. 3 , the specific gravity of material B is 8.05g / cm 3 , the specific gravity of tungsten carbide is 17.2g / cm 3 It is.
[0039] For test pieces Nos. 1 to 3, which used a welding material containing 50 vol % tungsten carbide with material A as the matrix material, the build-up layer was formed with laser outputs of 1000W, 800W, and 600W.
[0040] For test pieces 4 to 7 using material A as the matrix material and a welding material containing 40 vol% tungsten carbide, the build-up layer was formed at laser outputs of 1400W, 1000W, 800W, and 700W.
[0041] For test pieces 8 to 10, which used material A as the matrix material and a welding material containing 30 vol% tungsten carbide, the build-up layer was formed with laser outputs of 1000W, 800W, and 900W.
[0042] For test piece numbers 11 to 13, which used a welding material containing 50 vol % tungsten carbide with material G as the matrix material, the build-up layer was formed with laser outputs of 1000W, 800W, and 700W.
[0043] For test pieces 14 to 17 using material G as the matrix material and a welding material containing 40 vol% tungsten carbide, the build-up layer was formed at laser outputs of 1400W, 1000W, 800W, and 700W.
[0044] For test pieces Nos. 18 to 20, which used a welding material containing 30 vol% tungsten carbide with material G as the matrix material, the build-up layer was formed with laser outputs of 1000W, 800W, and 700W.
[0045] The test results are shown in Tables 4 and 5. The build-up layers of each test piece (test piece numbers 1 to 20) were observed by visual observation, penetrant testing (PT), cross-sectional observation, etc. Figures 4 and 5 are images showing the results of cross-sectional observation of the build-up layers. In Figures 4 and 5, arrows indicate areas where poor fusion or cracks have occurred between overlapping build-up layers. The "evaluation" in Tables 4 and 5 indicates the observation results of the build-up layers, with ◯ indicating "good," △ indicating "some areas that appear to be slightly defective," □ indicating "acceptable defects," and × indicating "defects that are visible by appearance."
[0046] [Table 4]
[0047] [Table 5]
[0048] For test piece No. 1, as shown in Figure 4(a), there was slight fusion failure where the buildup layers overlapped (overlapped area), and there were also areas where pores called blowholes had occurred in the buildup layer, but both were within the acceptable range. For test piece No. 2, as shown in Figure 4(b), there was unacceptable fusion failure in the overlapped area of the buildup layers, and PT showed what appeared to be a pattern indicating a defect, and defects were found in cross-sectional observation. For test piece No. 3, poor welding occurred, making it impossible to even perform a cross-sectional observation.
[0049] For test piece No. 4, unacceptable cracks occurred, as shown in Figure 4(c), and blowholes also occurred. In addition, the penetration rate of the build-up layer into the base metal was about 9.8%. For test piece No. 5, as shown in Figure 4(d), there was an acceptable lack of fusion in the overlapping part of the build-up layer. For test piece No. 6, not only was there an unacceptable lack of fusion in the appearance, but there was also a lack of fusion in the overlapping part of the build-up layer, as shown in Figure 4(e). For test piece No. 7, there was a welding failure, and even a cross-sectional observation was not possible.
[0050] For test piece No. 8, as shown in Fig. 4(f), acceptable fusion defects occurred in the overlapping part of the build-up layer. For test piece No. 9, unacceptable fusion defects occurred in the appearance, and fusion defects also occurred in the overlapping part of the build-up layer, as shown in Fig. 4(g). For test piece No. 10, as shown in Fig. 4(h), no noticeable defects were found.
[0051] From the results in Table 4 and Figure 4, it is found that in the test pieces (test piece numbers 1 to 10) in which the cobalt-based alloy contains a carbide-forming element, the tungsten carbide content in the weld metal is preferably 30 vol% or more, and laser cladding is preferably performed with a laser output of about 850 to 1050 W (more preferably 900 to 1000 W). It is also possible to suppress blowholes and poor fusion by forming an underlayer made of a material similar to the matrix material (base component) between the base material and the overlay layer.
[0052] For test piece No. 11, as shown in Fig. 5(a), there were areas in the overlapping part of the build-up layer that could have been defective, but they were within the acceptable range. For test piece No. 12, as shown in Fig. 5(b), no noticeable defects were found. For test piece No. 13, as shown in Fig. 5(c), there was a tolerable defective fusion in the overlapping part of the build-up layer.
[0053] For test piece No. 14, poor fusion occurred in the overlapping part of the build-up layer as shown in Figure 5(d), and the penetration rate of the build-up layer into the base metal was about 15%, but both were within the allowable range. For test piece No. 15, there was slight poor fusion in the overlapping part of the build-up layer as shown in Figure 5(e), but it was within the allowable range. For test piece No. 16, there was an allowable poor fusion in the overlapping part of the build-up layer as shown in Figure 5(f). For test piece No. 17, poor adhesion occurred, and even a cross-sectional observation was not possible.
[0054] For test piece No. 18, as shown in Fig. 5(g), a tolerable lack of fusion occurred in the overlapping portion of the build-up layer. For test piece No. 19, as shown in Fig. 5(h), a tolerable lack of fusion occurred in the overlapping portion of the build-up layer. For test piece No. 20, a welding failure occurred, and even a cross-sectional observation was not possible.
[0055] From the results in Table 5 and Figure 5, it is found that in the test pieces (test piece numbers 11 to 20) in which the cobalt-based alloy contains an element that forms an intermetallic compound, the tungsten carbide content in the weld metal is preferably 30 vol% or more, and laser cladding is preferably performed with a laser output of about 750 to 1450 W (more preferably 800 to 1400 W). It is also possible to suppress blowholes and poor fusion by forming an underlayer made of a material similar to the matrix material (base component) between the base material and the overlay layer.
[0056] Figure 6 is an image showing the cross-sectional observation result of the build-up layer when an underlay layer was formed. An underlay layer was formed on the surface of the base material, and then an overlay layer was formed on the surface of the underlay layer. The conditions for forming the overlay layer were the same as those in the above-mentioned examples. The material of the underlay layer was the same as that of the matrix material (base component).
[0057] The test results are shown in Table 6. For test pieces Nos. 21 to 23, which used a welding material containing 50 vol% tungsten carbide with material A as the matrix material, the build-up layer was formed on the surface of the underlayer with laser outputs of 600 W, 800 W, and 1400 W. For test pieces Nos. 24 to 26, which used a welding material containing 50 vol% tungsten carbide with material G as the matrix material, the build-up layer was formed with laser outputs of 600 W, 800 W, and 1400 W. The build-up layers of each test piece (test pieces Nos. 21 to 26) were observed by appearance observation, penetrant testing (PT), cross-sectional observation, etc. In Table 6, "Evaluation" refers to the observation result of the build-up layer, and indicates an evaluation based on the same criteria as in the above-mentioned examples.
[0058] [Table 6]
[0059] For test piece No. 21, as shown in Fig. 6(a), slight fusion defects occurred, but within the acceptable range. For test piece No. 22, as shown in Fig. 6(b), no noticeable defects were found. For test piece No. 23, as shown in Fig. 6(c), no noticeable defects were found, but there was a tendency for penetration to increase within the acceptable range.
[0060] For test piece No. 24, as shown in Fig. 6(d), slight fusion defects occurred, but within the acceptable range. For test piece No. 25, as shown in Fig. 6(e), no noticeable defects were found. For test piece No. 26, as shown in Fig. 6(f), no noticeable defects were found, but there was a tendency for penetration to increase within the acceptable range.
[0061] From the results in Table 6 and Figure 6, it can be seen that in the test pieces (test piece numbers 21 to 26) in which the cobalt-based alloy contains carbide-forming elements or intermetallic compound-forming elements, when an underlayer is formed between the base material and the build-up layer, laser cladding can be performed with a wide range of laser output of approximately 550 to 1450 W (more preferably 600 to 1400 W).
[0062] 5. Comparison with PTA Below, we explain the comparison between PTA (Powder Plasma Transferred Arc Welding) and laser cladding. Figure 7 shows images comparing PTA and laser cladding, where (a) shows a cross section of the buildup layer formed by PTA, and (b) shows a cross section of the buildup layer formed by laser cladding.
[0063] As shown in Figure 7(a), in the buildup layer formed by PTA, uneven distribution occurs due to the difference in specific gravity between the cobalt-based alloy and tungsten carbide, and the tungsten carbide settles to the bottom of the buildup layer. In contrast, as shown in Figure 7(b), in the buildup layer formed by laser cladding, there is no uneven distribution, and the tungsten carbide is dispersed throughout the buildup layer.
[0064] FIG. 8 is a schematic diagram showing a cross section of a buildup layer formed by PTA. As shown in FIG. 8, when a buildup layer is formed by PTA, the above-mentioned uneven distribution occurs in the overlapping portion of the buildup layer. As a result, a region P where the distribution amount of tungsten carbide is low occurs on the surface of the overlapping portion of the buildup layer. When a bath-in-shaft member on which such a buildup layer is formed is used, each region P wears with use, and bead-shaped partial wear occurs.
[0065] In this embodiment, by forming a build-up layer on the surface of the bath shaft member using laser cladding instead of PTA, it is possible to reduce the uneven dispersion caused by the specific gravity difference between the cobalt-based alloy and tungsten carbide, and form a build-up layer in which tungsten carbide is uniformly dispersed. This improves the wear resistance of the surface of the bath shaft member, preventing the occurrence of bead-shaped partial wear with use. [Explanation of symbols]
[0066] 1 Molten metal bath 2. Snout 3. Sink Roll 4 Support Roll 5 Rotation Axis 6 Rotation Axis 7 Sleeve 8. Bearings 9 Supporting member 81 Flange 100 Laser processing head 101 Laser Beam 102 Welding material 103 Shielding Gas 104 Irradiation position S steel plate
Claims
1. A method for producing a bath-in-bath shaft member for use in a molten metal plating bath, comprising the steps of: A method for manufacturing a bath-internal shaft member, comprising a cladding step of forming a cladding layer on a surface of the bath-internal shaft member by laser cladding using a composite alloy containing a cobalt-based alloy and tungsten carbide as a welding material.
2. The method for manufacturing a bath center shaft member according to claim 1 , wherein the cobalt-based alloy contains a carbide-forming element or an intermetallic compound-forming element.
3. The cobalt-based alloy includes a carbide-forming element; The method for manufacturing a bath center shaft member according to claim 2, wherein the content of the tungsten carbide in the melt is 30 vol% or more.
4. The method further includes a step of forming an underlay layer on the surface of the bath center shaft member, The method for manufacturing a bath-in-tube shaft member according to claim 3, wherein in the cladding step, laser cladding is performed on the surface of the underlayer with a laser output of 600 to 1400 W.
5. The cobalt-based alloy contains an element that forms an intermetallic compound, The method for manufacturing a bath center shaft member according to claim 2, wherein the content of the tungsten carbide in the melt is 30 vol% or more.
6. The method further includes a step of forming an underlay layer on the surface of the bath center shaft member, The method for manufacturing a bath-in-tube shaft member according to claim 5, wherein in the cladding step, laser cladding is performed on the surface of the underlayer with a laser output of 600 to 1400 W.
Citation Information
Patent Citations
Bearing device for rolls in molten metal plating bath
JP1993069155U